Coexistencia de Dendroctus frontaus Zimmerman y D. mexicanus Hopkins (Coleoptera: Scolytidae) sobre un mismo hospedero - Zúñiga, Gerardo; Cisneros, Ramón; Salinas, Yolanda (Instituto de Ecología, A.C., 1995)
We report a case of spatio-temporal cohabitation among two scolytid bark beetles Dendroctonus frontalis Zimmerman and D. mexicanus Hopkins on a single host. Results are analyzed according wíth their geographic distribution and reproductiva isolation. These data supports previous field observations and arise some questions respect to competition, reproduction, and reproductive isolation.